Extreme abundance ratios in the polluted atmosphere of the cool white dwarf NLTT 19868 - Kawka, Adela; Vennes, S. (Oxford University Press, 2016)
We present an analysis of intermediate-dispersion spectra and photometric data of the newly identified cool, polluted white dwarf NLTT 19868. The spectra obtained with X-shooter on the Very Large Telescope-Melipal show strong lines of calcium, and several lines of magnesium, aluminium and iron. We use these spectra and the optical-to-near-infrared spectral energy distribution to constrain the atmospheric parameters of NLTT 19868. Our analysis shows that NLTT 19868 is iron poor with respect to aluminium and calcium. A comparison with other cool, polluted white dwarfs shows that the Fe to Ca abundance ratio (Fe/Ca) varies by up to approximately two orders of magnitudes over a narrow temperature range with NLTT 19868 at one extremum in the Fe/Ca ratio and, in contrast, NLTT 888 at the other extremum. The sample shows evidence of extreme diversity in the composition of the accreted material: in the case of NLTT 888, the inferred composition of the accreted matter is akin to iron-rich planetary core composition, while in the case of NLTT 19868 it is close to mantle composition depleted by subsequent chemical separation at the bottom of the convection zone.